2015
DOI: 10.1016/j.ijdevneu.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of repetitive intermittent hypercapnic hypoxia on orexin in the developing piglet hypothalamus

Abstract: Orexin neuropeptides (OxA and OxB) and their receptors (OX1R and OX2R) are involved in maintenance of sleep and wakefulness, and are regulated by various environmental stimuli. We studied piglets, in the early neonatal period, exposed to 48-min of intermittent hypercapnic hypoxia (IHH; 7% O2/8% CO2) alternating with air. Three groups of 13-14 day-old piglets with IHH exposure of 1-day (1D-IHH) (n=7), 2-days (2D-IHH) (n=7) and 4-days (4D-IHH) (n=8) were compared to controls (exposed only to air, n=8). Immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…There are only a limited number of previous studies that have examined the effect of combined H/H on identified orexin neurons. Consistent with our findings, immunohistochemical results indicate that animals exposed to intermittent H/H have decreased expression of orexin-A and -B in lateral hypothalamus, as well as in dorsomedial hypothalamus and the perifornical area (Du et al 2016). The findings from a recent in vitro study (Williams et al 2007) conducted on mice showed that the change in bath solution from 10% to 5% CO 2 induces membrane hyperpolarization and decreases firing activity of orexin neurons in the lateral hypothalamus.…”
Section: Discussionsupporting
confidence: 91%
“…There are only a limited number of previous studies that have examined the effect of combined H/H on identified orexin neurons. Consistent with our findings, immunohistochemical results indicate that animals exposed to intermittent H/H have decreased expression of orexin-A and -B in lateral hypothalamus, as well as in dorsomedial hypothalamus and the perifornical area (Du et al 2016). The findings from a recent in vitro study (Williams et al 2007) conducted on mice showed that the change in bath solution from 10% to 5% CO 2 induces membrane hyperpolarization and decreases firing activity of orexin neurons in the lateral hypothalamus.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that Ox immunoreactivity is decreased in the hypothalamus and pons after IHH without changes in the total number of neurons in the C‐THT is consistent with findings reported after hypoxic or hypercapnic exposures alone (Table S2). In addition, the IHH data in this study provide confirmation of our previous work (Du et al ., ). Owing to the paucity of tissue available for all of the groups, a two‐dimensional counting method was used previously to determine the percentage of positive neurons, and we therefore only reported the percentage of Ox‐positive neurons, and not the total number of neurons.…”
Section: Discussionmentioning
confidence: 97%
“…According to the literature, excitation of Ox-positive neurons is mediated by intermittent rather than continuous hypoxia (Yamaguchi et al, 2015), but exposure to intermittent hypoxia must be coupled with hypercapnia before decreased Ox immunoreactivity is observed (Du et al, 2016). Neither intermittent hypoxia alone nor severe hypoxia promote decreased Ox immunoreactivity (Hundahl et al, 2011;Yamaguchi et al, 2015).…”
Section: Effects Of Ihhmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results from this study, both orexin receptor expressions (orexin receptors 1 and 2) are increased in the PVN after intermittent exposure to H/H (Hunt et al, 2013). The authors speculated that upregulation of these orexin receptors is the result of decreased level of orexin release and receptor density compensation due to H/H exposures (Du et al, 2016). Similar results have been obtained with acute exposure to hypercapnia alone.…”
Section: Discussionmentioning
confidence: 99%